Patrones de hipercementosis y su relación con posibles factores etiológicos locales en radiografías de individuos de una población mexicana - Bernal Ruiz, María Alejandra (2023)
Objective: Hypercementosis (HPC) is an asymptomatic pathology that, according to the existing literature, has a low prevalence, there is a lack of information and research on it, within these studies, few are made by ethnic groups. To determine the prevalence and radiographic patterns of this condition, as well as the analysis of the relationship of the pathology with some of what are considered possible local triggering factors (FDL) in Mexican individuals. Methodology: 1193 orthopantomographies (OPG) were analyzed, randomly selected from patients of both sexes, with a chronological age range between 18 and 90 years, identifying the prevalence of HPC, as well as its relationship between age groups, its morphological patterns (focal, diffuse and sleeve-shaped), its distribution by anatomical region and dental organs (ODs) and the association of its presence with possible local triggering factors. Results: 348 DO with HPC were found in a total of 194 patients (16.30%), with no relevant differences between genders (P> 0.05). There was a significant increase with respect to the presence of HPC in relation to the increase in the age of the patients (P= 0.001), finding it present in 10% of the age group <40 years, in 20.30% in the group of 40 to 60 years and > 60 in 30.20%. It was found more frequently in a diffuse form (75.28%), followed by the focal pattern (19.54%) and finding the sleeve-shaped morphology less common (5.17%). The mandible presented the greatest number of ODs with the presence of HPC, 136 (39.08%), with the left side being the most affected with 86 OD. The dental group with the greatest involvement was that of molars and premolars. Conclusions: The prevalence of hypercementosis was 16.30% in the Mexican individuals evaluated. Its presence increases as the age of the patients advances. Its main location is the mandibular region with a predilection for premolars and molars. Even though the idiopathic origin is the most frequent, it was observed that dental impaction is a possible local triggering factor.